Inelastic spectra for infilled reinforced concrete frames. - Dolsek, Matjaz
In two companion papers a simplified non-linear analysis procedure for infilled reinforced concrete frames is introduced. In this paper a simple relation between strength reduction factor, ductility and period (R-u-T relation) is presented. It is intended to be used for the determination of inelastic displacement ratios and of inelastic spectra in conjunction with idealized elastic spectra. The R-u-T relation was developed from results of an extensive parametric study employing a SDOF mathematical model composed of structural elements representing the frame and infill. The structural parameters, used in the proposed R-u-T relation, in addition to the parameters used in a usual (e.g. elasto-plastic) system are ductility at the beginning of strength degradation and the reduction of strength after the failure of the infills. Formulae depend also on the corner periods of the elastic spectrum. The proposed equations were validated by comparing results in terms of the reduction factors, inelastic displacement ratios, and inelastic spectra in the acceleration-displacement format, with those obtained by non-linear dynamic analyses for three sets of recorded and semi-artificial ground motions. A new approach was used for generating semi-artificial ground motions compatible with the target spectrum. This approach preserves the basic characteristics of individual ground motions, whereas the mean spectrum of the whole ground motion set fits the target spectrum excellently. In the parametric study, the R-u-T relation was determined by assuming a constant reduction factor, while the corresponding ductility was calculated for different ground motions. The mean values proved to be noticeably different from the mean values determined based on a constant ductility approach, while the median values determined by the different procedures were between the two means. The approach employed in the study yields a R-u-T relation which is conservative both for design and performance assessment (compared with a relation based on median values).
Keywords: Simplified non-linear analysis; Inelastic spectrum; Strength reduction factor; Inelastic displacement ratio; Infilled RC frame